2020
DOI: 10.3889/oamjms.2020.3784
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tooth Extraction Causes and Patterns

Abstract: PURPOSE: The purpose of this study was to investigate the causes and patterns of extraction of permanent teeth in the targeted population. METHODS: The study was conducted for a period of 11 months. An especially designed form was used to record the causes for extraction of a permanent tooth. Further, it was analyzed for age, gender, education, occupation, smoking, tooth position, endodontic treatment, chewing, esthetics, needs replacement, type of existing prosthesis, and causes for extraction. The vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…This is possibly due to salivary pooling protecting the lower teeth ( Cunha-Cruz et al, 2013 ). Similar findings were observed in other studies with more frequent extraction of maxillary teeth compared to mandibular ones ( Shareef et al, 2020 ). However, other reports have discovered that compared to maxillary molars, mandibular molars are more frequently extracted ( Sahibzada, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is possibly due to salivary pooling protecting the lower teeth ( Cunha-Cruz et al, 2013 ). Similar findings were observed in other studies with more frequent extraction of maxillary teeth compared to mandibular ones ( Shareef et al, 2020 ). However, other reports have discovered that compared to maxillary molars, mandibular molars are more frequently extracted ( Sahibzada, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…8 Sharif et al reported 9.9% cases with impaction problems in contrast to our study which reported only 1.46% of cases. 9 Other reasons for extraction in our study included failed root canal therapy, supernumerary teeth which accounted for 2.01% of cases similar to the study by Sahibzada et al 6 With regards to tooth type, the most commonly extracted tooth was first molar followed by second molar. This finding was in agreement with Passarelli et al where they reasoned it to the anatomical development of molar tooth that results in the formation of grooves and fissures making them more susceptible to dental caries.…”
Section: Discussionsupporting
confidence: 77%
“…1 Tooth extraction is an act of removing teeth from the alveolar and carried out if there is an indication that the tooth cannot be restored or maintained. 2,3 After the extraction action, it will leave a wound where the action was carried out and around it. 4 Wounds in tooth extraction have an opportunity for infection due to bacteria in the mouth.…”
Section: Introductionmentioning
confidence: 99%